2007
DOI: 10.1038/sj.npp.1301616
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping and Distinct Brain Regions Associated with the Anxiolytic Effects of Chlordiazepoxide and Chronic Fluoxetine

Abstract: Little is known about the sites of action for the behavioral effects of chronic antidepressants. The novelty-induced hypophagia (NIH) test is one of few animal behavioral tests sensitive to acute benzodiazepines and chronic antidepressants. The goals of these experiments were to examine patterns of brain activation associated with the behavioral response to novelty and identify regions that could regulate the anxiolytic effects of acute benzodiazepine and chronic antidepressant treatments, measured using the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 45 publications
1
33
1
Order By: Relevance
“…Neuronal activity has been shown to correlate with the expression of the early immediate gene, c-fos (40,41). Further, c-Fos expression in the BLA is selectively down-regulated by both acute benzodiazepine and chronic antidepressant treatment in rats performing similar behavioral paradigms (42), suggesting that c-Fos is a reliable marker for activity in circuits involved in anxiety-related phenomena. We used immunohistochemical techniques to measure c-Fos expression in the amygdala 90 min after the 10-min epoch spent approaching and avoiding the milk in the threatening context (i.e., the novel cage) of the novelty-induced hypophagia paradigm (43).…”
Section: Resultsmentioning
confidence: 91%
“…Neuronal activity has been shown to correlate with the expression of the early immediate gene, c-fos (40,41). Further, c-Fos expression in the BLA is selectively down-regulated by both acute benzodiazepine and chronic antidepressant treatment in rats performing similar behavioral paradigms (42), suggesting that c-Fos is a reliable marker for activity in circuits involved in anxiety-related phenomena. We used immunohistochemical techniques to measure c-Fos expression in the amygdala 90 min after the 10-min epoch spent approaching and avoiding the milk in the threatening context (i.e., the novel cage) of the novelty-induced hypophagia paradigm (43).…”
Section: Resultsmentioning
confidence: 91%
“…Longterm treatment of rats with either paroxetine (Muigg et al, 2007) or citalopram (Kuipers et al, 2006) did not increase c-Fos in any brain region examined, including the CeA. In contrast, Bechtholt et al (2008) showed that long-term fluoxetine increased c-Fos in multiple brain areas including the BNST, cingulate cortex, anterior NAc, and hippocampus and long-term mirtazapine treatment increased c-Fos in the CeA and dentate gyrus (Gerrits et al, 2006). There are very few studies that examined the effects of antidepressant drug treatments on ⌬FosB.…”
Section: Downloaded Frommentioning
confidence: 91%
“…In general, increases have not been reported in the DRN although Fraga et al (2005) found an increase after short-term administration of fluoxetine. Most studies show increases in c-fos or c-Fos in the CeA and BNST after short-term administration of different classes of antidepressants (Beck, 1995;Fraga et al, 2005;Slattery et al, 2005;Bechtholt et al, 2008). Longterm treatment of rats with either paroxetine (Muigg et al, 2007) or citalopram (Kuipers et al, 2006) did not increase c-Fos in any brain region examined, including the CeA.…”
Section: Downloaded Frommentioning
confidence: 99%
“…The NSF test is a test of anxiety and has previously been shown to be sensitive to chronic anti-depressant treatment (Bechtholt et al, 2008;Dulawa et al, 2004;Santarelli et al, 2003). Longer latency to eat in a novel environment is associated with increased anxiety.…”
Section: Novelty Suppressed Feeding (Nsf) Testmentioning
confidence: 99%